PENYUSUNAN LAPORAN LABA RUGI RUMAH MAKAN NASI EMPAL BU MARIE - Nariman, Augustpaosa; Massidy, Alan Octama (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
In carrying out its business activities, every company, both small, medium and large companies, really needs accounting calculations to produce financial reports. The financial statements produced by the company include a statement of financial position and a statement of income. Companies generally need an income statement to see how the business is performing and as a basis for making business decisions. The income statement provides information on how much company turnover can be generated and the costs that have been incurred in terms of obtaining sales revenue. The excess between revenue and costs will provide information that the company is experiencing a profit. Nasi Empal Bu Marie is a restaurant business with a franchise system using its original name Nasi Empal Bu Marie in Semarang. Nasi Empal Bu Marie in Jakarta is classified as an UMKM which was founded in July 2022 with 7 employees. The Company still uses simple records and is done manually. Statement of profit and loss are not made regularly every month. Companies need guidance and training to prepare profit and loss reports to find out the company's financial condition, the condition of stocks of goods that are recorded and more controlled as well as more measurable financial information to make decisions. Lecturer of FEB Untar majoring in Accounting conducts the one-day training, which went well with the aim that administrative employees can understand how to record sales transactions in a routine and structured manner and company owners can obtain financial information and business performance.